2022
DOI: 10.4269/ajtmh.21-1185
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Soil-Transmitted Helminth Infections among Primary School Children in the States of Chhattisgarh, Telangana, and Tripura, India, 2015–2016

Abstract: Soil-transmitted helminth (STH) infections are highly prevalent in many developing countries, affecting the poorest and most deprived communities. We conducted school-based surveys among children studying in first to fifth standard in government schools in the Indian States of Chhattisgarh, Telangana, and Tripura to estimate the prevalence and intensity of STH infections during November 2015 and January 2016. We adopted a two-stage cluster sampling design, with a random selection of districts within each agro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Compared to our study, increased moderate-heavy intensity STH infections have been reported from Myanmar [ 44 ], Malaysia [ 45 ], Cameroon [ 46 ], and Rwanda [ 47 ]. Contrary, decreased moderate-heavy intensity STH infections have been reported from India [ 48 ], Ethiopia [ 37 ], and Nigeria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our study, increased moderate-heavy intensity STH infections have been reported from Myanmar [ 44 ], Malaysia [ 45 ], Cameroon [ 46 ], and Rwanda [ 47 ]. Contrary, decreased moderate-heavy intensity STH infections have been reported from India [ 48 ], Ethiopia [ 37 ], and Nigeria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%